ORGANIZATIONAL LEARNING FROM THE PRODUCTION CHAIN OF TRANSPORT OF FREIGHT BY ROAD IN VALLE DEL CAUCA: VARIABLES OF SATISFACTION OF MEMBERS OF THE CANAL - Mosquera Abadia, Henry Alberto; Bedoya Ospina, Carolina; Cardenas, Ricardo Alonso; Gomez Sierra, Catherine (Cuadernos de Administración, 2008)
This article !Jresents the organizational learning of the productive chain of transport of freight by road, in Valle del Cauca, through knowledge of the variables of satisfaction of their members. The variables of satisfaction or dissatisfaction, concepts developed by Churchill and Suprenant (1982), which argue that conceptually the satisfaction is the result of buying and resuitll1g of using, comparing the rewards and costs of the purchase with relation to the consequences to expected or anticipated by the purchaser. [n this case its present the variables of satisfaction of the productive chain transport of freight by road in Valle del Cauca, they were organized into five (5) groups as follows: Standardization and operational, Culturals, Economics and Technological Aspects. This chain is made up of the following links up to know: Freight Generator, Transport Enterprise or carrier (vehicle owner) and Final Costumer. For purposes of analysis especially were considered the two (2) first links up.